Modeling monetary economies - Champ, Bruce; Freeman, Scott; Haslag, Joseph H. (New York, NY Cambridge University Press, 2022)
"Thoroughly updated and expanded with a new chapter on block chain and increased coverage of cryptocurrency, as well as new data, this established advanced undergraduate textbook approaches the subject via first principles. It builds on a simple, clear monetary model and applies this framework consistently to a variety of monetary questions. Starting with trade being mutually beneficial, the authors demonstrate that money makes people better off, and that government money competes against other means of payments, including other types of government payments. After developing each of these topics, the book tackles the issue of money competing against other stores of value, examining issues associated with trade, finance, and modern banking. From simple economies to modern economies, the authors address the role banks play in making more trade possible, concluding with the information problems plaguing modern banking"--
Contents: The economy and the planner's solution - - Equilibrium trade in the economy without money - - A simple model of money - - Barter and commodity money - - Inflation - - International monetary systems - - Price surprises - - Capital and banking - - Liquidity and financial intermediation - - Central banking and the money supply - - Money stock fluctuations - - Fully backed central bank money - - Payment systems - - Bank risk - - Liquidity risk and bank panics - - Deficits and the national debt - - Savings and investment - - The effect of the national debt on capital and savings - - The temptation of inflation.
Revised edition of the authors' Modeling monetary economies, 2016.
Includes bibliographical references and index.
Keywords: Money -- Mathematical models; BUSINESS & ECONOMICS / Economics / Macroeconomics